Multiband LTE power amplifier for handset application / Jagadheswaran Rajendran - Jagadheswaran, Rajendran (2015)
As wireless communication standard continues to evolve accommodating the demand of high data rate operation, the design of RF power amplifier (PA) becomes ever challenging. PAs are required to operate more efficiently while maintaining stringent linearity requirement. In this work, a new circuit to extend the linear operation bandwidth of a LTE (Long Term Evolution) power amplifier, while delivering a high efficiency is presented. The 950μm x 900μm monolithic microwave integrated circuit (MMIC) power amplifier (PA) is fabricated in a 2μm InGaP/GaAs process. The PA consists of three stages, which is the pre-driver, driver and main stages. The main stage is designed in class-J configuration in order to improve the efficiency of the PA. The optimum conduction angle method is employed to enable the PA to operate in bias condition which has the optimum operation for linearity and efficiency. A novel on-chip analog pre-distorter (APD) is designed and integrated into the driver stage to improve the linearity of the highly efficient PA further to meet the adjacent channel leakage ratio (ACLR) and error vector magnitude (EVM) specifications for LTE signal profile with 20MHz channel bandwidth. Experimental result verifies that the designed PA is capable to meet the ACLR specifications of -30dBc from 1.7GHz to 2.05GHz which encapsulates LTE Band 1,2,3,4,9,10,33,34,35,36,37 and 39 at maximum linear output power of 28dBm. The maximum EVM at 28dBm for 16-QAM scheme is 3.38% at 2050MHz.The corresponding power added efficiency (PAE) varies from 40.5% to 55.8% across band. With a respective input return loss of less than -15dB, the PA’s maximum power gain is measured to be 35.8dB while exhibiting an unconditional stability characteristic from DC up to 5GHz. The proposed architecture serves to be a good solution to improve the linearity and efficiency of a PA for wideband LTE operation without sacrificing other critical performance metrics. This will ultimately reach the goal to have single chip solution for handset LTE PA.